MENTAL HEALTH IN PRIMARY HEALTH CARE: AN EXPERIENCE REPORT ON OCCUPATIONAL STRESSORS IN A BASIC HEALTH UNIT - Santos Rocha Novais, Elines; Clara Jorge Cavalcante, Maria; Correia Maciel, Gabriel; Eduarda Chaves Silva, Maria; Janaína do Nascimento, Maria; Juan Nogueira Alencar , Vitor; Almeida da Silva, Flaelma; de Lima, Diana (Health and Society, 2025)
This experience report originates from a university extension project developed between August and December 2024, aimed at analyzing occupational stress and stressors experienced by healthcare professionals at the Dr. José Ramos Neto Basic Health Unit, in Eunápolis, Bahia, Brazil. The extension activity involved students and professors in the health field, integrating education, service, and community through investigative actions with a quantitative and qualitative approach. Data collection included the application of the Lipp Stress Symptom Inventory for Adults (ISSL), as well as a questionnaire on occupational stressors. Fourteen health professionals participated in the study, and the responses revealed that biological risk was the main stressor identified (34.6%), followed by the physical structure of the unit (23%). The data also indicated that 28.57% of the participants experienced some level of stress, with the resistance phase being the most prevalent. The extension experience provided a critical reflection on the mental health of professionals in Primary Health Care, highlighting the need for institutional interventions aimed at preventing occupational illness and reinforcing the role of extension activities in promoting social awareness, professional training, and humanized care.